KEMAMPUAN KOMPETISI BEBERAPA VARIETAS KEDELAI (GLYCINE MAX) TERHADAP GULMA ALANG-ALANG (IMPERATA CYLINDRICA) DAN TEKI (CYPERUS ROTUNDUS) - Gayuh Prasetyo Budi; Oetami Dwi Hajoeningtijas (JURNAL LITBANG PROVINSI JAWA TENGAH, 2009)
The objective of this research was to study response of the growth and yield on soybean varieties against Imperata cylindrica and Cyperus rotundus competition and to study competitive ability of soybean varieties against Imperata cylindrica and Cyperus rotundus. The experimental research was conducted at Karangsari Village, Kembaran, Banyumas. The experiment used a Randomized Completely Block Design with 2 factors and 4 replications. Factor 1. Soybean Variety, consisted of Grobogan, Ijen and Sinabung, Factor 2. Weed, consisted of clean weeding, Imperata cylindrica 50 weeds/m2 and Cyperus rotundus 50 weeds/m2. The result showed that Ijen and Sinabung caused the better growth than Grobogan. Sinabung caused the highest for the amount of polong per plant : 285.5 and the seed weight per plant : 46.6667 g. Sinabung caused the best competitive ability than Grobogan and Ijen, its showed that the highest competition value. The competition of Sinabung-Cyperus rotundus caused competition value : 15.0075, whereas the competition of Sinabung-Imperata cylindrica caused competition value : 7.9913.